Comprehensive Sensory Integration in Corrective Work with Children with Autism Spectrum Disorders Using the Senspace Method - Latysheva, Kateryna (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study was to investigate the effectiveness of the Senspace comprehensive sensory integration method as a community-applied intervention, utilizing standardized health technology tools for assessment Methodology: The research employed a quasi-experimental design in a community rehabilitation setting involving 50 children with ASD aged 4-7 years. The experimental group (n=25) received the 10-week Senspace program. Standardized health technology instruments (Sensory Profile, Vineland-3) and observational scales were used for evaluation. Main Findings: Statistically significant improvements were observed across all evaluated indicators within the experimental group. Notable reductions in sensory hypersensitivity were recorded: tactile sensitivity decreased by 16.5%, vestibular sensitivity by 19.1%, and proprioceptive processing by 19.7%. Indicators of social-communicative skills exhibited marked improvement: contact initiation increased by 83.3%, and joint attention improved by 84.6%. The overall adaptive score on the Vineland-3 demonstrated a rise of 13.4%. Correlation analysis revealed strong links between the alleviation of sensory disorders and advancements in adaptive functioning (r ranging from -0.745 to -0.668, p<.001). Novelty/Originality of this study: The scientific novelty of this work resides in the formulation and empirical validation of a therapeutic intervention program that combined structured play practices with elements of behavioral therapy, specifically designed to cultivate communicative and cognitive functions.